TAT-mediated transduction of bacterial redox proteins generates a cytoprotective effect on neuronal cells - Balaban, Cecilia Lucía (2017)
Cell penetrating peptides, also known as protein transduction domains, have the capacity to ubiquitously cross cellular membranes carrying many different cargos with negligible cytotoxicity. As a result, they have emerged as a powerful tool for macromolecular delivery-based therapies. In this study, catalytically active bacterial Ferredoxin-NADP+ reductase (LepFNR) and Heme oxygenase (LepHO) fused to the HIV TAT-derived protein transduction peptide (TAT) were efficiently transduced to neuroblastoma SHSY-5Y cells. Proteins entered the cells through an endocytic pathway showing a time/concentration dependent mechanism that was clearly modulated by the nature of the cargo protein. Since ferredoxin-NADP+ reductases and heme oxygenases have been implicated in mechanisms of oxidative stress defense, neuroblastoma cells simultaneously transduced with TAT-LepFNR and TAT-LepHO were challenged by H2O2 incubations to judge the cytoprotective power of these bacterial enzymes. Accumulation of reactive oxygen species was significantly reduced in these transduced neuronal cells. Moreover, measurements of metabolic viability, membrane integrity, and cell survival indicated that these cells showed a better tolerance to oxidative stress. Our results open the possibility for the application of transducible active redox proteins to overcome the damage elicited by oxidative stress in cells and tissues.